GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 1456 species occurrences available in GBIF matching the query: TaxonKey: Castilleja arvensis Cham. & Schltdl.. The dataset includes 1456 records from 97 constituent datasets: 62 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 1 records from UFG - Herbário da Universidade Federal de Goiás. 1 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 3 records from Vascular Plant Herbarium, Oslo (O). 1 records from FCAB - Herbário Friburguense. 1 records from UPCB - Herbário do Departamento de Botânica. 13 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 4 records from HAS - Herbário Alarich Rudolf Holger Schultz. 1 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 2 records from OUPR - Herbário "Professor José Badini". 22 records from Herbario Universidad de Antioquia (HUA). 20 records from UA Herbarium. 3 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 1 records from HPBR - Herbário Padre Balduino Rambo. 1 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from HPL - Herbário do Jardim Botânico Plantarum. 2 records from Herbario del CIBNOR. 2 records from MBML-Herbario - Herbário Mello Leitão. 2 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 1 records from Digital Florula - Las Cruces Biological Station. 10 records from PACA-AGP - Herbarium Anchieta. 10 records from NMNH occurrence DwC-A. 1 records from SMDB - Santa Maria Departamento de Biologia. 12 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 19 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Harvard University Herbaria. 16 records from Instituto de ciencias naturales. 42 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 3 records from Instituto de Botánica Darwinion. 1 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 2 records from MEXU/Colección Histórica. 2 records from Herbarium - Las Cruces Biological Station. 31 records from Especímenes INBio. 7 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 13 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 15 records from MBM - Herbário do Museu Botânico Municipal. 1 records from FUEL - Herbário da Universidade Estadual de Londrina. 16 records from Field Museum of Natural History (Botany) Seed Plant Collection. 4 records from IAC - Herbário do Instituto Agronômico de Campinas. 5 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 27 records from Bernice P. Bishop Museum. 441 records from Missouri Botanical Garden. 31 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 25 records from Naturalis Biodiversity Center (NL) - Botany. 4 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 1 records from CONN. 20 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 27 records from Instituto de Ciencias Naturales. 1 records from Lista florística preliminar de Tamaulipas. 4 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 3 records from Herbario de la Universidad Industrial de Santander. 2 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 4 records from SPSF - Herbário Dom Bento José Pickel. 43 records from herbario. 2 records from HUFU - Herbarium Uberlandense. 37 records from CAS Botany (BOT). 14 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 115 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 5 records from Geographically tagged INSDC sequences. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 7 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 71 records from Phanerogamic Botanical Collections (S). 2 records from FURB - Herbário Dr. Roberto Miguel Klein. 1 records from HVAT - Herbário do Vale do Taquari. 5 records from iNaturalist research-grade observations. 17 records from Herbarium of The New York Botanical Garden. 6 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from Geneva Herbarium – General Collection (G). 9 records from Herbarium de Geo. B. Hinton, México. 3 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 4 records from SysTax - Herbaria. 8 records from ICN - Herbário do Instituto de Ciências Naturais. 1 records from Flora vascular del cerro El Zamorano. 6 records from MEXU/Colección de Plantas Acuáticas. 2 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 43 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 2 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 38 records from Repatriación de datos del Herbario de Arizona (ARIZ). 1 records from Allan Herbarium (CHR). 1 records from R - Herbário do Museu Nacional. 8 records from Natural History Museum (London) Collection Specimens. 19 records from Colección del Herbario PSO de la Universidad de Nariño. 1 records from Herbario de la Universidad de Arizona, EUA. 1 records from Herbarium areqvipense (HUSA). 10 records from UEC - Herbário da Universidade Estadual de Campinas. 4 records from CESJ - Herbário Leopoldo Krieger. 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 4 records from Nationaal Herbarium Nederland.
Keywords: GBIF; biodiversity; species occurrences